Storage related changes in pizza cheese as affected using S. boulardii adjunct culture - Bihola, Ankit; Jana, Atanu; Rajani, Bhargav; Adil, Shaikh (Indian Journal of Dairy Science, 2025)
The investigation examined the storage related changes in Pizza cheeses for a period of 28 days at 4oC. The physicochemical properties (i.e. moisture, TA, pH, SN, TVFA) were markedly affected by T, P and the interaction T×P. The TA, SN and TVFA exhibited marked increases with the advancement of the storage period. The sensory scores markedly differed from each other with regard to T and P, except for stinginess. The stringiness score was markedly affected by T, P and the interaction T×P. Microbial analysis revealed the absence of coliforms in fresh and stored cheeses. The S. boulardii and LAB counts were markedly affected by T, P and the interaction T×P. The S. boulardii and LAB counts of all cheeses tended to show a gradual decrease during the storage period. Cheese CBHM was associated with a higher S. boulardii count and elicited the desired baking and sensory characteristics. Since storage beyond 14 days led to a reasonable decline in the count of S. boulardii, only 2 weeks of storage is advocated to provide health benefits from the consumption of cheese CBHM.